Pembentukan Perppu Cipta Kerja Dalam Perspektif Negara Hukum Demokrasi - Sandy Sulistiono; Widyawati Boediningsih (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Article 1 of the 1945 Constitution of the Republic of Indonesia states that the State of Indonesia is a legal state which has sovereignty in the hands of the people and is implemented according to the Constitution. In order to implement the principles of the State of Indonesia in accordance with the 1945 Constitution of the Republic of Indonesia, there is a guiding instrument, namely the provisions for the formation of laws in Law Number 12 of 2011 and their amendments which maintain legal certainty in Indonesia. However, the existence of the Job Creation Law which was followed by a Government Regulation in Lieu of a Job Creation Law (Perppu) is in fact not in accordance with the Constitution and Law Number 12 of 2011 so that this research examines the benchmarks regarding compelling interest circumstances in Perppu and the relationship between the formation of Perppu with the principles of the Unitary State of the Republic of Indonesia. Because this research is legal research, the approach used is a statutory approach related to the formation of Indonesian laws and regulations supported by the concept of a rule of law and a democratic state based on Pancasila.